The nature of Saemaul Undong as a rural development strategy: Topic modelling and text mining analysis - Choi, Young-Chool; Kee, Younghwa (Iberoamerican Journal of Science Measurement and Communication, 2024)
Objective. This study aims to identify the core characteristics of Saemaul Undong, which was applied as a strategy for rural development in Korea, to analyse the role of government in the implementation process of this policy, and to put forward some implications for the developing countries to be able to apply its principles and the government’s roles for their own rural development. Design/Methodology/Approach. The methods applied to the analysis are text mining analysis and topic modelling analysis, which are widely used in the field of social sciences nowadays. The data employed in this study are the guidelines regarding implementing the Saemaul Undong policy, which was drawn up by former president Park Chung Hee. Results/Discussion. As a result of the analysis, it may be said that the core characteristics of Saemaul Undong policy include: emphasis on the role of Saemaul Undong leaders, financial support from the Government, cooperation of villagers, support from public officials, a spirit of self-help, and movement to promote rural development. Conclusions. In conclusion, it is expected that the principles and implementation methods of the Saemaul Undong policy implemented in Korea in the 1970s can be applied to developing countries suffering from poverty in the future if they are appropriately modified to suit the conditions of developing countries. Originality. So far, the important principles of Saemaul Undong's policy have not been studied through topic modeling, so fundamental principles have not been derived. This study has great significance because it systematically derived core principles through the topic modeling method.